Geochronology Methods and Case Studies - Morner, Nils-Axel (IntechOpen, 2014)
Chronology is the backbone of history, and there is a wise saying stating there is no history without a chronology. Earths evolutionary history is built up by geochronology, i.e. time benchmarks upon which the geological history is built up step by step over its total time period of about 4.5 billion years. The first marker in this history is the Jack Hills zircon from Australia dated at about 4.4 GA. The most detailed records come from seasonal changes within annual varves. Stratigraphy provides the basic chronological ordering of layers by layers, units by units, fossil assemblage by assemblage, varves by varves, growth zone by growth zone, etc. The radiometric techniques implied the introduction of absolute age determinations. This book includes a combination of methodological presentations and related case studies, from where we learn about practical problems and achievements. Therefore, the book should be of basic interest both for scientists in their practical in field and laboratory, as well as for general educational purpose.